Socioeconomic determinants of access to health services among older adults: a systematic review - Ana Paula Santana Coelho Almeida; Bruno Pereira Nunes; Suele Manjourany Silva Duro; Luiz Augusto Facchini
ABSTRACT OBJECTIVE The objective of this study was to analyze the association between the socioeconomic characteristics and the access to or use of health services among older adults. METHODS This is a systematic review of the literature. The search has been carried out in the databases PubMed, LILACS and Web of Science, without restriction of dates and languages; however we have included only articles published in Portuguese, English, and Spanish. The inclusion criteria were: observational design, socioeconomic factors as variables of interest in the analysis of the access to or use of health services among older adults, representative sample of the target population, adjustment for confounding factors, and no selection bias. RESULTS We have found 5,096 articles after deleting duplicates and 36 of them have been selected for review after the process of reading and evaluating the inclusion criteria. Higher income and education have been associated with the use and access to medical appointments in developing countries and some developed countries. The same association has been observed in dental appointments in all countries. Most studies have shown no association between socioeconomic characteristics and the use of inpatient and emergency services. We have identified greater use of home visits in lower-income individuals, with the exception of the United States. CONCLUSIONS We have observed an unequal access to or use of health services in most countries, varying according to the type of service used. The expansion of the health care coverage is necessary to reduce this unequal access generated by social inequities.